2016
DOI: 10.1016/j.neuro.2016.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Blood levels of trace metals and amyotrophic lateral sclerosis

Abstract: Some trace metals may increase risk of amyotrophic lateral sclerosis (ALS), whereas others may be beneficial. Our goal was to examine associations of ALS with blood levels of selenium (Se), zinc (Zn), copper (Cu), and manganese (Mn). We conducted a case-control study of 163 neurologist confirmed patients from the National Registry of Veterans with ALS and 229 frequency-matched veteran controls. We measured metal levels in blood using inductively coupled plasma mass spectrometry and estimated odds ratios (ORs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 42 publications
2
38
0
1
Order By: Relevance
“…Corroborating this, Roos et al (37) found low plasma zinc content in patients with ALS. Moreover, Peters et al (38), in a case-control study, observed an inverse association between serum zinc concentration and ALS. This association was stronger in those with worse function, suggesting that zinc may play a role in the etiology of ALS and that supplementation with this mineral may benefit these patients.…”
Section: Discussionmentioning
confidence: 93%
“…Corroborating this, Roos et al (37) found low plasma zinc content in patients with ALS. Moreover, Peters et al (38), in a case-control study, observed an inverse association between serum zinc concentration and ALS. This association was stronger in those with worse function, suggesting that zinc may play a role in the etiology of ALS and that supplementation with this mineral may benefit these patients.…”
Section: Discussionmentioning
confidence: 93%
“…Including such factors as occupation, heavy metals, petro‐chemicals, organophosphate/pesticides26, 27, 28, 29, 30 and possible influence of electromagnetic field (EMF)18, 25, 31 and military service 32. Although not all studies related to ALS have consistently reported environmental factors,33 the majority have highlighted environmental factors rather than longevity4, 5, 6, 7, 8, 18, 25, 26, 27, 28, 29, 30 as well as epigenetic changes,33, 34, 35 whist recently, research had linked rises in dementias to proximity to major roads 30…”
Section: Discussionmentioning
confidence: 99%
“…Дефицит Zn в организме больных ОА усугубляется при наличии инсулинорезистентности с метаболическим синдромом, а тот, в свою очередь, усиливает процессы свободнорадикального окисления в артикулярных тканях [12,19]. Низкий уровень Zn является фактором риска поражений периферической нервной системы, а содержание этого МЭ в крови никак не связано с концентрациями Cu, Mn и Pb [15]. Через систему цинксвязывающего белка металлотионеина недостаток в организме больных РА и ОА Zn определяет повышенный синтез синовиоцитами провоспалительных цитокинов -туморонекротического фактора α, интерлейкина-6 и -17 [3].…”
Section: результатыunclassified